Comparison between First and Second Language Learning. Working Papers on Bilingualism, No. 7 - Macnamara, John.; Ontario Inst. for Studies in Education, Toronto. Bilingual Education Project ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The thesis of the paper is that the process of learning a second language, if successful, is the same as that of learning a first one. The paper discusses various objections that have been raised against this thesis, and it discusses the considerable body of research which explores it. It examines the appropriateness of the research data for throwing light on the validity of the thesis. It concludes with some practical guidelines for language teachers drawn from observations of babies learning their mother tongue. (Author)
ERIC Note: For related documents, see FL 007 646-651.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Bilingualism; Child Language; Interference (Language); Language Acquisition; Language Instruction; Language Research; Learning Processes; Native Speakers; Second Language Learning; Reports, Research